KICK-START LITERACY FOR ALL. COMPARATIVE RESULTS FROM ROMANIAN PREPARATORY GRADE CLASSROOMS - Bianca BALEA; Maria KOVACS; Codruţa TEMPLE (National Centre for Policy and Evaluation in Education, 2023)
Research shows that reading performance in the early grades is a strong predictor of reading ability throughout the school years, and is therefore likely to impact children's academic and career trajectories, with those of children coming from disadvantaged socio-economic backgrounds being negatively impacted (Cunningham & Stanovich, 1997; Dolean et al., 2019). Using a comparative approach, the present study aimed to determine whether there were differences in literacy skills development in children from low socio-economic backgrounds who received specifically developed emergent literacy instruction (intervention group, IG) and those who did not (control group, CG). The literacy program was developed based on recent scientific evidence (Bear, 2022) emphasizing the importance of the following in emergent literacy instruction: concepts about print (1), alphabet and letter-sound knowledge (2), concept of word (3), phoneme awareness (4), and word recognition (5). The intervention took place in the 2021-2022 school year, over an 8-month period, and consisted of using emergent literacy assessments, as well as literacy learning materials developed specifically for the preparatory grades. The total sample consisted of 300 children in 25 preparatory grade classes, divided between intervention and control groups (260 and 40 students, respectively), who were all assessed on the five abovementioned emergent literacy concepts and skills, pre- and post-intervention. ANOVA analyses were conducted to test for differences between children in the two groups. Results highlight significant differences in terms of literacy development, with children in IG showing higher scores on all the five measures than children in the CG.